La evolución en el concepto de propiedad en la doctrina social de la iglesia - García Salvattecci, Hugo (2011)
The Pontifical Social Doctrine expressed its explicit recognition of the private property as a legitimate right corresponding to every man: to possess, provide and enjoy the goods resulting from work. This right is fundamental and inalienable, since it is based in the human nature. The Church, through its Pontifical Doctrine, particularly from Pope León XIII when mentioning the subject related to the private property did not assume a new concept, but basing on the Holy Scriptures as well as in the tradition, mentioned what it thought regarding the exercise of this right, separating it from the exclusive and holy character. It has also said that if this right must be recognized by the State; its exercise should not represent detriment in other people's right, nor threaten against commonwealth, which is called the full society.